Institutional Support as a Correlate of Staff Job Commitment in Public University Libraries in Bayelsa State, Nigeria - Gloria Aboma (INTERNATIONAL JOURNAL OF SOCIAL SCIENCES AND MANAGEMENT RESEARCH, 2026)
This study examined institutional support as a correlate of staff job commitment in public university libraries in Bayelsa state, Nigeria. It is a correlational study and the correlational survey research design was adopted for the study. Total population was 100 librarians in Public University libraries in Bayelsa state, Nigeria, made up of professionals and para-professionals. Total enumeration was used for the study. Five research questions guided the study and five hypothesis were tested at 0.05 alpha level. Data were collected using structured questionnaire. The study adopted the Pearson Product Moment Correlation to analyze the research question and test the hypothesis. Findings indicated that there exists a high and significant correlation between institutional support and staff job commitment in Bayelsa State, Nigeria. It was recommended that Universities should enhance staff welfare by providing health insurance, housing allowances, transport benefits, and flexible work policies to improve commitment. Also Institutions should improve supervisor support by training supervisors in mentorship, communication, and employee engagement to boost staff morale and commitment.